The conceptual modeling in the process of computer-assisted generation of data warehouse models (2014)
This paper introduces the methodological guidelines for the data warehouse model computer assisted generation. These guidelines are divided into four different stages: information analysis, conceptual model and logical design are the first ones and the last one occurs within them and it is known as the traceability stage. These stages describe a data warehouse design proposal can be obtained from the inherited operational systems (E/R). One of the main stages we considered to be important is the data warehouse conceptual model. This paper goes deeper into the different ways to obtain the conceptual model from the logical structure of the institutional inherited systems, taking into account that these systems generally use a relational model in its structure. In order to accomplish this, it is proposed to use the interrelation among entities to generate a graph of interrelation of attribute and then apply a set of design rules to obtain the conceptual model.